Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor XYZ - Teddy Shandro Sihombing; Taat Kuspriyono; Yunidyawati Azlina (MAMEN: Jurnal Manajemen, 2025)
This study aims to analyze the influence of the work environment and work discipline on employee performance at XYZ Office. The background of this research stems from the real conditions observed in the workplace, including limited facilities, poor interpersonal relationships, and recurring disciplinary violations such as tardiness, low responsibility, and lack of communication ethics. The research employed a quantitative approach using a survey method and inferential statistical analysis. The population consisted of 40 employees, all of whom were included as samples using a saturated sampling technique. Data were collected through observation and questionnaires, then analyzed using SPSS version 25. The results indicate that the work environment has a positive and significant effect on employee performance, with a t-value of 4.151 greater than the t-table value of 2.026, while work discipline also has a significant influence with a t-value of 4.724 > 2.026. Simultaneously, both variables significantly affect employee performance, supported by an f-value of 132.380 > 3.24 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.877 indicates that 87.7% of the variation in employee performance is explained by the work environment and discipline, while the remaining 12.3% is influenced by other factors. These findings emphasize that a supportive and safe work environment, combined with consistent and fair discipline, plays a vital role in improving employee performance in public institutions.